The rights and wrongs of private schooling - John White (Future in Educational Research)
Abstract This is a discussion, from a largely global but partly British perspective, about whether private schools should be freely permitted, discouraged or abolished. This, it is claimed, depends on the kind of private school one has in mind. The paper moves on to three arguments against British private schools, especially prestigious so‐called ‘public schools’: that they promote social exclusiveness, have created a ruling élite, and are unjust. This latter claim, which also has global relevance, is explored in some detail. The meritocratic conception of society which it presupposes is then also discussed and criticised. The final section of the paper is about future perspectives on private schooling across the world. It looks at proposed and actual measures to abolish or curtail them; educational proposals to limit the power of meritocracy, including reforms to the school examination system. It also discusses how likely it is that suggested reforms of any of these kinds will actually take place.